A study on gait pattern of malay subjects - Basah, Rina Hary Ani Osman (Universiti Sains Malaysia, 2006)
Gait pattern is also known as walking pattern. The gait pattern of each individual is unique. The various terms and factors used in gait pattern analysis include direction line, step length, step width, gait angle, gait line or gait length, foot angle, foot length, foot width and also presence of any peculiarities in the foot or gait pattern. This research involves the study of individual's walking pattern. The individuality is observed by measuring the variables stated above. The frequency, mean, standard deviation and standard error of mean are calculated. The results show the variety and distribution of data in the frequency table. In this study all variables are discussed separately. Based on the measurements and its calculation, this study reveals the identification of the individual. Recognizing people by their gait is a biometric of increasing interest. Recently, analysis has progressed by the evaluation of few techniques on small databases with encouraging results to large databases and still with encouraging results. The potential of gait as a biometric was encouraged by the considerable availability of evidence, especially in biomechanics and literature. In this study, gait pattern provides useful information in number of ways. The most frequent and important use of gait pattern is to identify the originator. Bare foot prints are highly individualistic in nature like fingerprint. In the same way the study of gait pattern also reveals the individual identification. This gait pattern research also indicates a mean to establish sex, and height of the person to some extent. By careful analysis of the gait pattern, we can also indicate the presence of deformity, speed and also any possibility of fraudulent act by criminals. For this research study, I have collected one hundred samples of gait pattern from Malay population and conducted my study and recorded the fmdings.